Pengaruh Literasi Keuangan, Akses Permodalan, dan Minat Menggunakan E-Commerce Terhadap Kinerja UMKM (Studi Kasus pada Pelaku UMKM di Kota Kediri) - Rahma Nur Hamida; Nur Diana; Junaidi Junaidi (Universitas Islam Malang, 2023)
This study aims to determine the effect of financial literacy, access to capital and interest in using e-commerce on the performance of MSMEs in Kediri City. This research is a quantitative research with a correlational research approach. The population in this study were SMEs registered at the Kediri City Cooperatives and SMEs Office and the sample in this study was 75 respondents with a sampling technique using purposive sampling. The data used in this study is primary data in the form of questionnaires distributed to respondents via Google Form and measured using a Likert scale. The analysis used in this study is multiple linear regression analysis. The results of this study indicate that (1) financial literacy has a positive and significant effect on MSME performance, (2) access to capital has a positive and significant effect on MSME performance and (3) interest in using e-commerce has a positive and significant effect on MSME performance.Keywords: UMKM performance, financial literacy, access to capital, e-commerce